Foliage penetration radar detection and characterization of objects under trees - Davis, Mark E. 1945- (SciTech Pub., 2011)
The book reviews developments in the following fields: History of battlefield surveillance; foliage penetration SAR collection system; FOPEN SAR image formation; radio frequency interference suppression; FOPEN target detection and characterization; FOPEN SAR design; FOPEN ground moving target indication; and bistatic FOPEN SAR.
Keywords: Ground penetrating radar.; Forest canopies.; Earth (Planet) -- Surface -- Remote sensing.; Aerial observation (Military science); elektronické knihy; electronic books